MASCOTS 2001, Proceedings Ninth International Symposium on Modeling, Analysis and Simulation of Computer and Telecommunication
DOI: 10.1109/mascot.2001.948869
|View full text |Cite
|
Sign up to set email alerts
|

Performing file prediction with a program-based successor model

Abstract: Recent increases in CPU performance have surpassed those in hard drives. As a result, disk operations have become more expensive in terms of the number of CPU cycles spent waiting for them to complete. File prediction can mitigate this problem by prefetching files into cache before they are accessed. Identifying relationships between individual files plays a key role in successfully performing file prefetching. It is well-known that previous patterns of file references can be used to predict future references.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The other, the model based on recently accessing information typical representatives: LS (Last Successor) model using the latest successor to the current accessing file as the prediction results, based on LS models constructed PLS [19] model, ULS [20] model and PULS [21] model. In these prediction models, the main use of the file attributes include the number of users to access the file, the size of the requested data, the time characteristic, file access times (repeatability) and I/O operation types etc.…”
Section: File Activity Predicted Modelmentioning
confidence: 99%
“…The other, the model based on recently accessing information typical representatives: LS (Last Successor) model using the latest successor to the current accessing file as the prediction results, based on LS models constructed PLS [19] model, ULS [20] model and PULS [21] model. In these prediction models, the main use of the file attributes include the number of users to access the file, the size of the requested data, the time characteristic, file access times (repeatability) and I/O operation types etc.…”
Section: File Activity Predicted Modelmentioning
confidence: 99%
“…However, if a file is not in the cache, the system works out to fetch this file to cache. T. Yeh and S. Brandt [7,8,9] present a Program-Based Successor (PBS) model, which identifies relationships between individual files through the names of the programs accessing them. They base their design on the assumption that relationships between files are caused by program and programs access almost the same files in roughly the same order every time they execute.…”
Section: Related Workmentioning
confidence: 99%
“…The problem is not new and is in fact worsening as recent increases in CPU and memory speeds have exceeded those in physical disks [11]. On the other hand, studies [8,9,10] have shown that file access behavior is not random, and therefore, two main techniques can be used to work out the latency problem, namely caching and prefetching. Caching keeps in memory the data that are the most likely to be used again, while prefetching attempts to bring data in memory before they are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Yeh et al [15] investigated a simple but effective successor model that identifies the relationships between files through identification of the programs accessing them.…”
Section: Previous Workmentioning
confidence: 99%